Two Early 19th-Century Malay Documents from Cabau - Gallop, Annabel Teh (PENDETA, 2021)
This article presents and discusses the texts of two early 19th-century Malay documents from Cabau, on the Kesang river, now in the state of Melaka, which were seen and copied by C.O. Blagden in about 1894 in the house of the Penghulu of Cabau. The sealed commissions were presented to the Penghulu of Cabau by the Temenggung Paduka Tuan of Muar, charging the Penghulu to ensure the holding of communal prayers (sembahyang berjemaah) in the region of Cabau. As rare surviving examples of texts on the internal governance of a Malay territory, these documents are valuable for the study of Malay diplomatics and chancery practice. As historical sources, they also cast light on the regulation of Islamic life on the west coast of the Malay peninsular, and on the lineage of the Temenggungs of Muar.